The Effect Of Big Ball Game Modification On Gross Motor Development Of Elementary School Students - Rahma Dewi (UNIVERSITAS NEGERI MAKASSAR, 2023)
The purpose of this study was to determine the effect of playing big ball on increasing the gross motor development of elementary school students. The research method used pre-experimental with One Group Pre-test and Posttest Design. The population totalled twelve people using the total sampling technique to obtain ten samples. The data analysis technique used the paired t-test with the SPSS version 16 program. The test results for the Gross Motor Development (TGMD-2) instrument had a value of p = 0.000, and all of these data had a value of p <0.025 so there was a significant difference in the results of the ability test. the basic motion before and after being given treatment. This study concludes that the big ball modification game is effective in improving the gross motor skills of elementary school students. Suggestions that can be given are the innovation in the provision of motion learning material which is very necessary so that the goals of developing children's gross motor skills can be achieved.